Developing a Bright NIR‐II Fluorophore with Fast Renal Excretion and Its Application in Molecular Imaging of Immune Checkpoint PD‐L1. (22nd October 2018) - Wan, Hao; Ma, Huilong; Zhu, Shoujun; Wang, FeiFei; Tian, Ye; Ma, Rui; Yang, Qinglai; Hu, Zhubin; Zhu, Tong; Wang, Weizhi; Ma, Zhuoran; Zhang, Mingxi; et al.
Abstract: Fluorescence imaging in the second near‐infrared (NIR‐II) window holds impressive advantages of enhanced penetration depth and improved signal‐to‐noise ratio. Bright NIR‐II fluorophores with renal excretion ability and low tissue accumulation are favorable for in vivo molecular imaging applications as they can render the target‐mediated molecular imaging process easily distinguishable. Here, a probe (anti‐PD‐L1‐BGP6) comprising a fluorophore (IR‐BGP6) covalently bonded to the programmed cell death ligand‐1 monoclonal antibody (PD‐L1 mAb) for molecular imaging of immune checkpoint PD‐L1 (a targeting site upregulated in various tumors for cancer imaging) in the NIR‐II window is reported. Through molecular optimization, the bright NIR‐II fluorophore IR‐BGP6 with fast renal excretion (≈91% excretion in general through urine within the first 10 h postinjection) is developed. The conjugate anti‐PD‐L1‐BGP6 succeeds in profiling PD‐L1 expression and realizes efficient noninvasive molecular imaging in vivo, achieving a tumor to normal tissue (T/NT) signal ratio as high as ≈9.5. Compared with the NIR‐II fluorophore with high nonspecific tissue accumulation, IR‐BGP6 derived PD‐L1 imaging significantly enhances the molecular imaging performance, serving as a strong tool for potentially studying underlying mechanism of immunotherapy. The work provides rationales to design renal‐excreted NIR‐II fluorophores and illustrate their advantages for in vivo molecular imaging. Abstract : By optimizing the molecular structure, a bright second near‐infrared (NIR‐II) fluorophore IR‐BGP6 exhibiting fast renal excretion kinetics is developed. Benefiting from the low tissue accumulation, high brightness, and advantages of imaging in the NIR‐II window, the anti‐PD‐L1‐BGP6 conjugate demonstrates efficient molecular imaging of immune checkpoint PD‐L1 in vivo, providing a potential probe for in‐depth study of underlying mechanism of immunotherapy.